The indicative effects of apolipoproteins on organic erectile dysfunction: bridging Mendelian randomization and case-control study - Zhang, Zhexin; Yan, Mo; Li, Yuezheng; Pan, Yang; Wang, Shangren; Xu, Mingming; Zhou, Hang; Liu, Xiaoqiang (Frontiers in Endocrinology, 2024)
The existing research on the association between apolipoproteins (Apos) and erectile dysfunction (ED) primarily relies on observational studies and does not distinguish between organic and psychogenic causes when diagnosing ED. It is difficult to believe that Apos play a role in psychogenic ED. To address these issues, our study explored the causal relationship between lipoproteins and ED using Mendelian randomization (MR) analysis and differentiate between organic and psychogenic ED through the use of nocturnal penile tumescence and rigidity (NPTR) monitoring. Multivariate MR analysis revealed significant causal associations between high-density lipoprotein (HDL), Apo A1, and Apo B/A1 with ED (OR and 95% CI were 0.33 (0.14-0.78), 3.58 (1.52-8.43), and 0.30 (0.13-0.66)). we conducted statistical and analytical analyses on the data of 212 patients using multivariate analyses and receiver operating characteristic (ROC) curves. Patients with organic ED had significantly lower levels of HDL, Apo A1 and Apo A1/B, whereas patients with organic ED had considerably higher levels of Apo B and low-density lipoprotein (LDL). The diagnostic value of Apos in predicting the risk of organic ED was evaluated using ROC curves. The results indicated that Apo A1 and Apo A1/B demonstrated good predictive value. HDL, Apo A1, and Apo A1/B have been identified as risk factors for ED in our study. Furthermore, our research highlights the significance of Apo A1 and Apo A1/Apo B in the development of organic ED and suggests their potential use as indicators to assess the risks associated with organic ED.